Repair of vesicouterine fistula by not using traditional o connor method (Journal of the Pakistan Medical Association, 2020)
Abstract A 25-year-old female patient visited our clinic with complaint of cyclic haematuria. She had previous two Caesarean Sections at a secondary care hospital. Her complete urinalysis showed abundant red blood cells. Through computed tomography a fistula tract between the posterior wall of the bladder and the anterior wall of the lower uterine segment was diagnosed. The Cystoscopy revealed a fistulous opening with a diameter of nearly 1.5 cm localized between the bladder and uterine cavity. Fistulae was repaired by abdominal approach without transection of bladder. Surgery was performed by mobilization of bladder and wide anterior uterine dissection. A 2cm defect in the lower uterine segment was identified and was closed with 0 polyglycolic acid suture. Bladder defect was repaired in two layers. Then omental tissue flap was placed between the two surfaces. At 6 months follow the up patient was asymptomatic. Keywords: cyclic menouria; vesicouterine fistulas; Youssef’s syndrome. Continuous..